Planning in The Perspective of Islamic Education Management (Study of the Qur’an Surah Al-Hasyr [59] verse 18) - Adi Fadli; Awaluddin Awaluddin (Institut Agama Islam Negeri (IAIN) Curup, 2022)
The purpose of this paper is to find the meaning of planning that is written and implied in the Qur’an, which led to the success of a prophet and apostle, Muhammad saw. Apart from a miracle from Allah swt., one of his successes is managing well. The indicator is found in the planning by the Prophet. In this article, to analyze surah al-Hasyr [59] verse 18 through a qualitative descriptive research method with data sources from the library (library research) and the main data source is the Qur'an, where it was also done with an interpretation approach based on the interpretation of al-Misbah, al-Qurtubi, ath-Thabari, al-Azhar, ibn Kathir, al-Bayan ruh, al-Maraghi, al-Mubin, and al-Qur’an wa I’rabuh wa Bayanuh, it is then related to planning from the perspective of Islamic education management. The results conclude that Islam teaches various aspects of life that cannot be separated from the rules of Allah swt. as stated in the Qur’an surah al-Hasyr [59] verse 18, which explains that the planning must be adjusted to the conditions of the past, present, and future. In preparing a plan, is not only for worldly goals but must go beyond the boundaries of the targets of worldly life. Focus on that planning to achieve the world target of happiness and hereafter so that both can be achieved in a balanced way. Therefore, to predict the future requires careful planning, even though the final result will all happen only by the will of Allah swt.